Bowel Management in Spinal Cord Injury Patients - Hughes, Matthew (Clinics in Colon and Rectal Surgery, 2014)
Spinal cord injuries are common in the United States, affecting approximately 12,000 people per year. Most of these patients lack normal bowel function. The pattern of dysfunction varies with the spinal level involved. Most patients use a bowel management program, and elements of successful programs are discussed. Surgical treatment, when indicated, could include sacral nerve stimulation, Malone antegrade continence enema, and colostomy.
Keywords: spinal cord injury; neurogenic bowel; bowel management program